2009
DOI: 10.2214/ajr.08.1413
|View full text |Cite
|
Sign up to set email alerts
|

Background Fluctuation of Kidney Function Versus Contrast-Induced Nephrotoxicity

Abstract: We identified a high incidence of acute kidney injury among control subjects undergoing unenhanced CT. The incidence of creatinine elevation in this group was statistically similar to that in the isoosmolar contrast medium group for all baseline creatinine values and all stages of chronic kidney disease. These findings suggest that the additional risk of acute kidney injury accompanying administration of contrast medium (contrast-induced nephrotoxicity) may be overstated and that much of the creatinine elevati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
116
1
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(143 citation statements)
references
References 39 publications
7
116
1
12
Order By: Relevance
“…Mortality, incidence of CKD, and requirements for RRT did not differ between contrast-exposed and unexposed patients. Our study, similar to many others, [4][5][6][7] has found equivalent incidences of AKI between contrast-exposed and unexposed patients and challenged whether the current definition of CIAKI represents a true clinical entity.…”
Section: Is Contrast Exposure Necessary and Sufficient For Ciaki?supporting
confidence: 88%
“…Mortality, incidence of CKD, and requirements for RRT did not differ between contrast-exposed and unexposed patients. Our study, similar to many others, [4][5][6][7] has found equivalent incidences of AKI between contrast-exposed and unexposed patients and challenged whether the current definition of CIAKI represents a true clinical entity.…”
Section: Is Contrast Exposure Necessary and Sufficient For Ciaki?supporting
confidence: 88%
“…Our patient population was drawn from a comprehensive database of all CT substantial fraction of patients who, regardless of exposure to contrast material, experience post-CT AKI (2,16,17). This contributes noise to any CIN analysis, and many patients may be assigned a diagnosis of CIN when other nephrotoxic agents or conditions are to blame (16,17).…”
Section: Subjectsmentioning
confidence: 99%
“…This contributes noise to any CIN analysis, and many patients may be assigned a diagnosis of CIN when other nephrotoxic agents or conditions are to blame (16,17). The nonenhanced CT population has been used as a way to control for baseline post-CT AKI risk (2,(5)(6)(7)(8)(9)(10), but this is insufficient because it does not address the numerous risk factors for CIN (eg, diabetes mellitus or pre-CT AKI), in addition to chronic renal insufficiency, that may cause iodinated contrast material to be withheld. Because a large fraction of patients who are examined with nonenhanced CT have nephrotoxic risk factors that are directly responsible for the clinical avoidance of contrast material, the nonenhanced and contrast-enhanced CT populations are fundamentally different.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…And third, no control group of patients who were submitted to CT without CM was analyzed and compared with their population. This is a major flaw of the study because an increase in serum creatinine concentration has already been described in non-critically ill patients who had a CT scan without CM administration [5]. Performing such analyses would allow one to estimate the attributable impact of CM injection on renal function impairment.…”
mentioning
confidence: 99%